The Challenges Of Writing: English Education Students At STAI Miftahul Ulum Tanjungpinang - Eka Mayasari; Joko Iswanto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to identify the problems faced by English education students at STAI Miftahul Ulum in writing courses. The background of this research is based on the importance of writing skills in the academic world and the challenges faced by students in mastering linguistic, cognitive, psychological, and learning environment aspects. This research uses a qualitative approach with the Focus Group Discussion (FGD) and observation methods. The research subjects were second, fourth, and sixth-semester students in the 2023 academic year who had taken Basic Writing, Editing & Revising Erroneous Text, and Academic Writing courses. The results showed that the main problems lie in grammatical errors and the organization of ideas related to linguistic aspects. Cognitively, students have difficulty developing ideas and drawing logical conclusions. Psychologically, low motivation and self-confidence exacerbate students' writing abilities. Meanwhile, an unsupportive learning environment, such as limited access to reading sources and minimal guidance from lecturers, becomes a significant external constraint. The conclusion of the study indicates that the appropriate solution involves intensive guidance in grammar, increased opportunities for writing practice, and the creation of an interactive learning environment. The results of this study are expected to contribute to the development of more effective and structured writing learning strategies.